2018
DOI: 10.1111/jphp.12872
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic fractions from nine Trifolium species modulate the coagulant properties of blood plasma in vitro without cytotoxicity towards blood cells

Abstract: The most efficient anticoagulant activity in plasma was found for T. fragiferum and T. incarnatum extracts, while the T. alexandrinum fraction was the most effective inhibitor of thrombin amidolytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
1
3
1
Order By: Relevance
“…alexandrinum extract showed strong activity towards aPTT even at concentrations as low as 3 mg/ml while no effect on PT was observed. The obtained aPTT activity was opposing to the previously obtained results that suggested that the plant did not affect the coagulation times (TT, PT or aPTT) (Kolodziejczyk-Czepas et al 2018). Difference in the sample preparation could be one of the reasons for the differences in the results as in our study we used the total ethanolic extract in in vitro testing; compared to using phenolic fractions in the mentioned study.…”
Section: Discussioncontrasting
confidence: 84%
“…alexandrinum extract showed strong activity towards aPTT even at concentrations as low as 3 mg/ml while no effect on PT was observed. The obtained aPTT activity was opposing to the previously obtained results that suggested that the plant did not affect the coagulation times (TT, PT or aPTT) (Kolodziejczyk-Czepas et al 2018). Difference in the sample preparation could be one of the reasons for the differences in the results as in our study we used the total ethanolic extract in in vitro testing; compared to using phenolic fractions in the mentioned study.…”
Section: Discussioncontrasting
confidence: 84%
“…In accordance with those findings reported in literature caffeic acid or its derivatives can be strong candidates for their observed effects on blood coagulation. Our findings were also in accordance with those reported in the literature [25][26][27][28][29][30]. The extracts with relatively high caffeic acid and other phenolic acids contents acted as an anti-coagulant substance.…”
Section: Hplc and Lc-qtof-ms Analysessupporting
confidence: 93%
“…Measurements were performed using a kinetic model, as described in our previous work [ 53 ]. Briefly, blood plasma was preincubated with the examined substances (at final concentrations of 10, 25, and 50 mg/L) for 15 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%